2020
DOI: 10.1007/s40119-019-00160-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Amyloidosis: A Survey of Current Awareness and Clinical Challenges Among Cardiologists in Switzerland

Abstract: Introduction Transthyretin amyloidosis (ATTR) is a progressive disease in which amyloid fibril deposition disrupts tissue structure and organ function. Many patients with ATTR present with cardiac involvement; recent studies indicate that ATTR prevalence is higher than expected in patients with certain heart conditions. Although long delays to diagnosis are common, recent treatment advances have made timely diagnosis critical to ensure appropriate patient management. Despite clinical guideline updates, it rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
4
18
0
Order By: Relevance
“…Our data are in line with the results reported by Mircsof et al among 72 Cardiologists working in Switzerland, that showed a wide variation in knowledge and in diagnostic tests used during differential diagnosis of ATTR CA, and concluded that Cardiologists in that country would benefit from information on the latest advances in ATTR 8 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are in line with the results reported by Mircsof et al among 72 Cardiologists working in Switzerland, that showed a wide variation in knowledge and in diagnostic tests used during differential diagnosis of ATTR CA, and concluded that Cardiologists in that country would benefit from information on the latest advances in ATTR 8 .…”
Section: Discussionsupporting
confidence: 93%
“…Being a relatively rarely diagnosed syndrome, the underdiagnosis may be related to the poor awareness of this disease among physicians, bringing to late or no diagnosis. However, little is known about the real knowledge of CA among physicians: a survey on physicians' attitudes in amyloidosis treatment has been recently performed 7 , while only one study assessed knowledge among cardiologists 8 . Given the late clinical manifestations of ATTRwt CA and its common presentation as heart failure, a clinical condition frequently treated by geriatricians 9 , it is pivotal for these specialists to suspect this disease when indicated.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 , 16 , 17 Nevertheless, the utility of 99m Tc‐labelled bone radiotracer scintigraphy as a diagnostic modality and the importance of early ATTR‐CM diagnosis have not yet been internalized as common practice by general cardiologists. 18 Moreover, the procedures for 99m Tc‐labelled bone radiotracer scintigraphy are highly variable among institutions. 19 These findings indicate a need for guidance on daily clinical scenarios to consider 99m Tc‐labelled bone radiotracer scintigraphy for a suspected diagnosis of ATTR‐CM, as well as a standardized protocol for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Reasons for diagnostic delay are multifactorial and include: disease rarity and phenotypic heterogeneity, lack of physician awareness, other disease mimicry, and until recently, a lack of sensitive non-invasive investigations. 16…”
Section: Treatment and The Implication Of Diagnostic Delaysmentioning
confidence: 99%